Parker Solar Probe Observations of Solar Wind Energetic Proton Beams Produced by Magnetic Reconnection in the Near‐Sun Heliospheric Current Sheet. Issue 9 (4th May 2022) - Phan, T. D.; Verniero, J. L.; Larson, D.; Lavraud, B.; Drake, J. F.; Øieroset, M.; Eastwood, J. P.; Bale, S. D.; Livi, R.; Halekas, J. S.; Whittlesey, P. L.; Rahmati, A.; et al.
Abstract: We report observations of reconnection exhausts in the Heliospheric Current Sheet (HCS) during Parker Solar Probe Encounters 08 and 07, at 16 R s and 20 R s, respectively. Heliospheric current sheet (HCS) reconnection accelerated protons to almost twice the solar wind speed and increased the proton core energy by a factor of ∼3, due to the Alfvén speed being comparable to the solar wind flow speed at these near‐Sun distances. Furthermore, protons were energized to super‐thermal energies. During E08, energized protons were found to have leaked out of the exhaust along separatrix field lines, appearing as field‐aligned energetic proton beams in a broad region outside the HCS. Concurrent dropouts of strahl electrons, indicating disconnection from the Sun, provide further evidence for the HCS being the source of the beams. Around the HCS in E07, there were also proton beams but without electron strahl dropouts, indicating that their origin was not the local HCS reconnection exhaust. Plain Language Summary: Magnetic reconnection in current sheets is a universal plasma process that converts magnetic energy into particle energy. The process is important in many laboratory, solar, and astrophysical plasmas. The heliospheric current sheet (HCS), which originates from the Sun and extends throughout the heliosphere, is the largest current sheet in the solar system. One of the surprises of the Parker Solar Probe mission is the finding that magnetic reconnection is almost always active in the near‐Sun HCS, despite its enormous scales. In this paper, we report direct evidence showing that reconnection in the HCS close to the Sun can be a source of energetic protons observed in the solar wind. The reason protons can be accelerated to high energies (to tens of kilo‐electronvolts) is because the available magnetic energy per particle is high close to the Sun. This finding is important because the source of energetic protons in the heliosphere is unknown. Key Points: Large available magnetic energy per particle led to significant proton acceleration by reconnection in the near‐Sun heliospheric current sheet (HCS) at 16 and 20 Rs Proton beams and strahl electron dropouts in separatrices are evidence for HCS being a source of energetic protons seen outside the HCS Energetic protons beams outside the HCS also exist without strahl electron dropouts. Their origin is unlikely to be the local HCS exhaust